A new approach for evaluating the water resistance of sunscreens on consumers: tap water vs. salt water vs. chlorine water. (29th March 2014) - Puccetti, G.; Fares, H.
Synopsis Objective An efficient sunscreen product needs to offer broad spectrum photostable UV protection during consumer use. Water resistance has become an additional criterion requested by consumers spending time near water or outdoors. Polymers generally provide water resistance to formulations and are critical to the formation and stability of a sunscreen film on skin when exposed to water. The present work introduces a new in vivo screening approach to measure water resistance using UVA‐induced fluorescence imaging. Methods The approach has been applied to several formulations containing different polymers and compared to commercial products, for the three main water types: tap, salt and chlorinated water. All testing has been performed on the forearms of 10 subjects using UVA imaging. In addition, the skin whitening has been measured for all formulations on five subjects when exposed to water by visible light imaging. Results Our approach showed clear differences in water resistance values among the formulations tested, reflecting the importance of the formulation and the polymers used. The method proved capable of discriminating not only sunscreen performances with different water proofing ingredients but also water specific sunscreens such as a beach dedicated product showing a 20% higher resistance to salt water vs. tap and chlorine waters. Conclusion The use of UVA‐induced fluorescence imaging on skin proved a useful in vivo approach for measuring the water resistance performances for various sunscreen lotions with a wide range of skin whitening effects in water. Our method showed how high water resistance can be combined in a Wet skin® sunscreen with superior non whitening effect on the skin.